Identification of performance requirements for user-centered design of running shoes - Clifton, P.; Burton, M.; Subic, A.; Perret-Ellena, T.; Bedford, A.; Schembri, A. (Procedia Engineering, 2011)
This research aims to identify design attributes of a new generation running shoe by relating key performance parameters to the requirements of a specific user group. This paper considers the first phase of the research, comprising user group profiling, as well as the selection and subjective quantification of appropriate performance variables for targeted user groups. Three user groups have been defined, with the key functional performance attributes identified and prioritised for each. Using this information it has been possible to form the basis of a functional design specification for a shoe that should be best suited to the needs of runners within the target user group.